Indications and Outcomes of Repeat Keratoplasty for Graft Failure at a Tertiary Eye Care Center in Nepal - Sapkota, Jyoti; Bajracharya, Leena; Gurung, Reeta; Rana, Rachana Singh (Nepalese Journal of Ophthalmology, 2023)
Introduction: Graft failure is a common complication following keratoplasty requiring repeat keratoplasty (re-KP). Objectives: To determine the indications and outcome of repeat keratoplasty at a tertiary eye care centre in Nepal. Materials and methods: This was a retrospective study of 78 patients who underwent re-KP for graft failure in Tilganga Institute of Ophthalmology from Jan 2015 to Dec 2020. Indications for the primary keratoplasty, causes of graft failure and outcomes of re-KP in terms of vision acuity, graft clarity and secondary glaucoma were evaluated. Cases of regraft with less than one-year follow-up period were excluded. Results: A total of 78 re-KPs had been performed in 78 patients during the study period. Seventy eyes had undergone single corneal regraft and 8 eyes had undergone multiple (second or third) regraft surgery. Most common indication of primary keratoplasty was infectious keratitis (n=36; 46.2%). On follow up, 36 eyes (46.2%) were clear at the last visit, of which 31 eyes were single regraft cases and 5 were of multiple regraft cases. Most common cause of graft failure was graft infection (n=34; 43.6%) followed by corneal scarring (n=12; 15.4%). Of 42 eyes with failed regrafts, recurrence of the preoperative infection was commonest cause (n=15, 35.7%) followed by secondary glaucoma (n=11; 26.2%). Of 36 eyes with clear regraft, only 4 eyes (11.11%) achieved best corrected vision of ≥6/18 and remaining 32 eyes had BCVA <6/18 due to associated cataract, secondary glaucoma and high astigmatism. Conclusion: The most common cause for re-KP includes graft infection followed by secondary glaucoma. Outcomes of corneal regrafts in the form of graft clarity and visual acuity are suboptimal.